Determinants Of Investment Portfolio Performance: A Systematics Literature Review - Yuliana, Rena; Siwiyanti, Leonita; Purnomo, Budi Supriatono; Purnamasari, Imas (The Eastasouth Management and Business, 2024)
A thorough grasp of the variables influencing portfolio performance is necessary given the significance of investment portfolio management in the face of shifting financial market dynamics. This study uses a method called the Systematic Literature Review (SLR) approach with an emphasis on Prefered Reporting Item for Systematic Review and Meta-Analysis (PRISMA) 2020, which has not been discovered in prior research on the same issue. The study highlights the importance of ratios like Sharpe, Treynor, Jensen, and Sortino in assessing investment portfolio success. It also highlights the impact of non-financial variables like household preferences on performance. Return is crucial, and diversification can lower risk and boost returns. The study emphasizes the use of Value-at-Risk (VaR) for dynamic risk evaluation.